Introducing managerialism into national educational contexts through pseudo-conflict: A discursive institutionalist analysis. (July 2019) - Avigur-Eshel, Amit; Berkovich, Izhak
Highlights: Finds that despite visible differences between the two policy discourses, they share core managerial assumptions and beliefs. Uses a new approach to propose a fresh perspective on the introduction of managerialism into national educational settings. Abstract: This article provides a fresh perspective on the introduction of global ideas, particularly managerialism, into national educational settings, based on insights of the discursive institutionalism approach. We argue that this introduction may occur as various policy actors promote different versions of managerialism, leading to a debate between education policy actors holding common managerialist assumptions and beliefs, in other words, a pseudo-conflict. The result is a conflict over education policy that is strictly bounded by shared assumptions and beliefs. We analyze the discourse of leading policy actors during two consecutive tenures of Israeli Education Ministers (2009–2013, 2013–2015), using parliamentary protocols and press interviews.